Cancer Communication and Partner Burden: An Exploratory Study. (25th November 2013) - Venetis, Maria K.; Magsamen‐Conrad, Kate; Checton, Maria G.; Greene, Kathryn
Abstract This exploratory article applies Communication Privacy Management theory to an examination of cancer‐related open communication, topic avoidance, and partner burden from the perspectives of patients and their partners. 2 models were proposed: 1 model considered participants' communication behaviors, and the other considered partners' perspectives of the other's topic avoidance. Participants include 95 dyads in which 1 partner had been diagnosed and/or treated for cancer. Variables of interest include: patient/partner open communication, patient/partner topic avoidance, patient/partner perceptions of other's topic avoidance, and partner burden. Data were analyzed using structural equation modeling. Results support relationships between openness, topic avoidance, perceived topic avoidance, and partner burden. The manuscript discusses implications of perspective, open communication, and topic avoidance on partner burden.